VISUAL PERSUASION AND BEHAVIOUR CHANGE: A STUDY OF VIEWERS’ RESPONSES TO TELEVISED HIV/AIDS ADVERTISEMENTS IN KENYA - Jacquiline, Ondimu (European Scientific Journal, ESJ, 2012)
Combating HIV/AIDS has been a great challenge in Kenya. One of the major obstacles that hinder the achievement of this Millennium Development Goal is; communication barrier. Little or no information, misinformation or misunderstanding regarding these diseases has contributed to this barrier. In an attempt to get the message to Kenyans, health communicators and non-governmental organisations have manipulated various linguistic techniques combining visuals and words to influence behaviour change. This paper examines the use of visuals in the Kenyan television to influence behavior change and how the viewers respond to these advertisements. The study will analyze television non-commercial advertisements related to HIV/AIDS in order to identify the role of visual messages in the management of this disease and explore how visual elements can modify, redefine or re-contextualize what is verbally communicated. The study employs the semiotic and cognitive theories of visual communication to unpack the implications inscribed in visual elements. The paper concludes that the use of alternative approaches with appropriate visuals and activities that stimulate and are interesting by health communicators can go a long way in motivating the desired behaviour change.